The Role of Religiosity on Employee Engagement and Performance: The Perspective of Muslim Employees - Anthony Brien; Dwi Suhartanto; Ira Siti Sarah; Tintin Suhaeni; Setiawan Setiawan; Aldy Mochammad Faiz Raksayudha (Politeknik Negeri Bandung, 2021)
Literature suggests that religiosity is an imperative factor in influencing a person's work. However, a lack of attention has been given to its effect on employee engagement and employee job performance. The purpose of this study is to assess the direct effect religiosity has on employee job performance and its indirect effect through employee engagement from the perspective of Muslim employees. To examine the religiosity-job performance model, this study utilizes Partial Least Squares (PLS) modelling with a sample of 569 Muslim employees in Bandung, Indonesia. This study reveals that religiosity dimensions (practice, altruism, and belief) significantly influence employee engagement. However, among the religiosity dimensions, only altruism has both a direct and indirect effect on employee engagement. While this unique study confirms the link between engagement and job performance, it offers a new understanding of the employee engagement role and the link between employee religiosity and employee job performance. With no previous studies in this area, it offers new insights and theoretical and managerial implications.